Lexical Bundles in Chinese Middle School English Language Teaching: Corpus and Pedagogical Insights - Zheng, Beiting (2025)
This study explores the use of lexical bundles (LBs) in the Chinese middle school English language teaching (ELT) context, focusing on ELT textbooks, high-stakes exams, and the influence of teachers’ attitudes on the application and challenges of using LBs in the classroom. Although LBs – high-frequency recurring fixed word sequences – have been shown to be crucial for learners of English as a second language (L2) in both spoken and written contexts, they are often overlooked in research as well as in the current curriculum and teaching practices in China. This study compares the highfrequency LBs found in Chinese middle school ELT textbooks with those in the British National Corpus (BNC) Sampler, which represents first language (L1) English contexts, as well as with the high-frequency LBs that appear in the Zhongkao (Hanzi: 中考, Middle School Scholastic Aptitude Examination). The results reveal that the LBs in the Chinese middle school textbooks not only fail to align with the high-frequency bundles in the L1 English corpus and the Zhongkao corpus, but also omit critical usage patterns evident in these contexts.